TINJAUAN PRAKTEK MUDHARABAH PERBANKAN SYARIAH DI INDONESIA - Irwin Ananta Vidada (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Along with the market potential of a large segment of Islamic banking in Indonesia as the largest Muslim country in the world, the preachers are supported by the MUI continuously broadcasts a message to forbid usury transactions. The preachers encourage Muslim communities and businesses to seek alternative financial institutions that promise free muamalah usury as product and services offered by the Islamic banking. Savings on Islamic banking products in general use mudharabah and contract wadi'ah. Services become the core business of Islamic banks is mudharabah and practices surrounding the contract is at the reviews on this article. However, there are indications mudaraba practice of Islamic banking in Indonesia is still found a number of irregularities even in common with the concept of conventional banks. This makes the practice of Islamic banking is still not completely aligned with the provisions of sharia. Indications of irregularities found any element of the contract mudharaba engineering, whereas mudharabah is the core business of Islamic banking itself. The contract engineering practices resulting transaction violates the provisions of sharia Islamic banks themselves then dragged on usurious transactions. Then the actual incidence is camouflage on savings or borrowing products with usury, but the sharia packaging services. Keywords: Mudharabah, Syariah Banking, Usury